Analysis of Characteristics, Information Motivation Behavioral Skills in HIV Patients to Improve Antiretroviral Adherence : A Cross-Sectional Study - Chairiyah, Royani; Setyaningsih, Widanarti (Universitas Ahmad Dahlan, 2024)
Background: The number of people with HIV/AIDS in Indonesia, particularly an east Jakarta still to be concerned. Clients in community who required antiretrovirals (ARVs) treatment has been identified in relation to client’s characteristics and Information Motivational Behavioral Skills (IMB), so it might improve client’s adherence ARV therapy. This study aims to analyze the adherence of taking ARV therapy within clients suffering HIV, who were taking ARV therapy at Kramat Jati District Community Health Center. Method: The study design was quantitative research with a cross-sectional approach. The population come from Kramat Jati district, and there are 74 respondents have been involved by purposive sampling technic. These respondents were undergoing ARV therapy at Kramat Jati Community Health Center from August 3 to November 24, 2022. The data was processed using the chi square test. Results: There were relationships between age characteristics (0.030), sex (0.013), occupation (0.035), marital status of respondents (0.009). There was a relationship between Information (0.004), Motivational (0.024), and Behavioral Skills (0.042) with adherence to taking ARV drugs in HIV/AIDS patients at the Kramat Jati Health Center). No association of educational characteristics (0441) with adherence to taking ARV drugs. Conclusion: there was a relationship of characteristics (age, gender, occupation, employment status), and the relationship of Information, Motivational and Behavioral Skills with adherence to taking ARV drugs. Information motivation behavioral skills that were very effective for adherence to taking ARV drugs in people with HIV. However, educational level had no correlation with client’s obedience in taking ARV therapy